Germline pathogenic variants in Mexican patients with hereditary triple-negative breast cancer - Yanin Chavarri-Guerra; Cynthia Villarreal-Garza; Ana S Ferrigno; Alejandro Mohar; Dione Aguilar; Rosa M Alvarez-Gomez; Lenny Gallardo-Alvarado; Azucena del Toro-Valero; Gregorio Quintero-Beulo; Francisco Gutierrez-Delgado; José Luis Rodriguez-Olivares; Maria Fernanda Ochoa-Chavez; et al. (Instituto Nacional de Salud Pública, 2022)
Objective. Describe the prevalence of breast cancer (BC)- associated germline pathogenic variants (PVs) among Mexican patients with triple-negative BC (TNBC). Materials and methods. The spectrum of PVs identified among patients with TNBC who were enrolled in a prospective registry and underwent genetic testing was analyzed. Results. Of 387 patients with invasive TNBC and a median age at diagnosis of 39 years (range 21-72), 113 (29%) were carriers of PVs in BC-susceptibility genes: BRCA1 (79%), BRCA2 (15%), and other (6%: ATM, BRIP1, PALB2, PTEN, RAD51C, and TP53). PV carriers were younger at BC diagnosis (37 vs. 40 years, p=0.004) than non-carriers. Conclusion. A large proportion of TNBC in Mexican patients is associated with germline PVs, the vast majority in BRCA. The incremental yield of PVs in other BC-susceptibility genes was modest, and a stepwise approach starting with BRCA testing may be justified if it is more cost-effective than multigene panel testing.